PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN MAULANA LAUNDRY - Nurfi'ah, Sulikatin (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to analyze the effect of service quality, price and location variables on customer satisfaction with Maulana Laundry. This study uses a quantitative causal approach. The population used is Maulana Laundry customers who have used laundry services 2 times. The sample used was 40 people with accidental sampling technique. The type of data used is primary data with a questionnaire method. The analytical technique used is multiple regression analysis with the help of SPSS 23. The results of the study show that service quality partially has a significant effect on customer satisfaction with a sig value. 0.001. And the price partially has no significant effect on customer satisfaction with the value of sig. 0.427. And the location partially has no significant effect on customer satisfaction with the value of sig. 0.277. Meanwhile, simultaneously the quality of service, price and location have a significant effect on customer satisfaction with the value of sig. 0.000.